Pengaruh Nilai Tukar dan Inflasi Terhadap Volume Ekspor Crude Palm Oil (CPO) Selama Masa Pandemi - Adi Irawan; Rika Veryana Madani Gurning (Politeknik Negeri Batam, 2023)
Crude Palm Oil (CPO) is a commodity owned by Indonesia with a large total export. The purpose of this research is to analyze the effect of exchange rate and inflation on CPO export volume. The approach used is a quantitative approach and the data processing uses the EViews (Econometric Views) 12.0 application. The data used is secondary time series data during the COVID-19 pandemic, namely monthly data for the 2019-2021 period. Based on the results of the multiple linear analysis used, it shows that the exchange rate has an insignificant effect on the volume of Indonesian CPO exports during the pandemic. This shows that during the pandemic, the decline in exports of the CPO commodity was driven by disruptions to international trade logistics which caused delays in the process of sending goods between countries. Meanwhile, inflation had a significant effect on CPO export volume during the pandemic. This means that inflation can cause price increases in commodity goods which will cause a decrease in demand for CPO.